2007
DOI: 10.1177/175899830701200201
|View full text |Cite
|
Sign up to set email alerts
|

Pain, Disability in Daily Activities and Work Participation in Patients with Traumatic Hand Injury

Abstract: Traumatic hand injuries are represented in a large proportion of the patients treated at the outpatient department of occupational therapy in the VU University Medical Centre, Amsterdam. Most of the patients are referred to occupational therapy by specialists in the hospital. Information about the course of traumatic hand injuries regarding performance of daily activities is still limited. Research, focused on problems experienced by patients with hand injuries, may contribute to a better understanding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…They are also often more force-demanding, for example cooking, cleaning, and work, and they can therefore provoke pain. This may explain why these problems are solved to a minor degree at 12 months as pointed out by Poerbodipoero (27).…”
Section: Progress In Occupational Performancementioning
confidence: 91%
See 1 more Smart Citation
“…They are also often more force-demanding, for example cooking, cleaning, and work, and they can therefore provoke pain. This may explain why these problems are solved to a minor degree at 12 months as pointed out by Poerbodipoero (27).…”
Section: Progress In Occupational Performancementioning
confidence: 91%
“…Little is told about the persisting performance problems in these patients and some authors have asked for more detailed information regarding the performance of daily activities since often only the DASH and other less client-centred instruments have been used in research (25,27). Using the client-centred assessment tool, the COPM, did in this study capture the client's self-perceived occupational performance, and new details were obtained concerning the changes in the number and types of performance problems throughout the first year after the fracture.…”
Section: Progress In Occupational Performancementioning
confidence: 99%
“…Their range of motion and strength have previously been described in detail (2,3). Pain, however, and performance problems in these patients with acute pain are only sparsely accounted for, and the influence of pain is mostly described at the level of function or tasks measured by coordination tests or structured questionnaires (4)(5)(6). Performance and performance problems can be categorized at several different levels of complexity.…”
Section: Introductionmentioning
confidence: 98%
“…As occupational therapists we often experience that also in patients with acute conditions pain has a negative influence on the activities and occupations in the patients' daily lives, as well as on the patients' active involvement in occupational therapy. Pain is thus a factor of vital importance in the occupational therapy intervention process, even though the pain in patients with orthopaedic injuries is expected to be diminished along with the reduction of the damage (1,2,5).…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] The combined use of objective clinical evaluation and self-reported scales in hand therapy practice ensures that rehabilitation focuses on individual needs. 23 The objective of this study was to explore the correlation between active range of motion and self-reported disability and function in patients treated through early mobilization after flexor tendon repair.…”
Section: Introductionmentioning
confidence: 99%